A method for linguistic metaphor identification - Steen, Gerard J (John Benjamins Pub. Co, 2011)
Includes bibliographical references and index; Preface -- Acknowledgements -- Linguistic metaphor identification in usage -- MIPVU: a manual for identifying metaphor-related words -- Metaphor identification in news texts -- Metaphor identification in conversation -- Metaphor identification in fiction -- Metaphor identification in academic discourse -- Metaphor identification in Dutch news and conversations -- Reliability tests -- From method to research: cleaning up our act -- Metaphor in English discourse: a corpus-linguistic approach -- The quality of evidence: from MIP to MIPVU -- Appendix -- Overview of annotated files from BNC-baby -- References -- Index